2012
DOI: 10.1590/s0102-311x2012000100009
|View full text |Cite
|
Sign up to set email alerts
|

Community violence and childhood asthma prevalence in peripheral neighborhoods in Salvador, Bahia State, Brazil

Abstract: (adjusted OR = 1.94;. The study highlighted the relevance of community violence as a risk factor for asthma and the need for further research to elucidate methodological issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
3
16
0
2
Order By: Relevance
“…Our study does not answer the question of how violence affects healthcare utilization, but it is proposed to disrupt caregiver coping strategies and erode decision-making competencies. 20 Research in traumaexposed populations shows that low-income urban caregivers often lack adequate resources to cope with traumatic experiences, leaving them vulnerable to depressive symptoms 39 and difficulties in fulfilling caregiving activities such as attending to their child's needs. 40 Caregivers who experience chronic exposure to traumatic events are at even greater risk for decreased parental effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study does not answer the question of how violence affects healthcare utilization, but it is proposed to disrupt caregiver coping strategies and erode decision-making competencies. 20 Research in traumaexposed populations shows that low-income urban caregivers often lack adequate resources to cope with traumatic experiences, leaving them vulnerable to depressive symptoms 39 and difficulties in fulfilling caregiving activities such as attending to their child's needs. 40 Caregivers who experience chronic exposure to traumatic events are at even greater risk for decreased parental effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study of Brazilian children aged 4-12 years with asthma identified youths who were exposed to high levels of violence to be twice more likely to experience asthma symptoms than their peers with no exposure. 20 The role of community violence in contributing to asthma disparities is thus a public health focus, but conceptual models for health disparities are also exploring protective influences at the community level. Informal social control, defined as the willingness of neighbors to intervene for common community goals, and social cohesion, which reflects high levels of trust and solidarity among neighbors that inhibit community violence, 21 were associated with higher levels of perceived health in Hispanic adolescents residing in Chicago and in an international sample.…”
Section: Introductionmentioning
confidence: 99%
“…61 We reported that physical or sexual abuse is associated with asthma morbidity in school-aged Puerto Ricans. 62 Exposure to violence has been associated with asthma or asthma symptoms among children in Brazil (aOR for symptoms=1.9, 95% CI 1.1 to 3.4) 63 and Puerto Rico, 38 and preliminary evidence suggests that this may be partly explained by ADCYAP1R1 methylation. 38 More recently, we showed that child stress may affect asthma morbidity by reducing bronchodilator response (BDR), and that an ADCYAP1R1 single-nucleotide polymorphism is associated with both reduced ADRB2 expression and reduced BDR.…”
Section: Psychosocial Stressmentioning
confidence: 99%
“…Violence exposure has been associated with numerous health risks including obesity, asthma, liver disease, heart disease and chronic obstructive pulmonary disease (Alves, Santos, Feitosa, & Barreto, 2012; Centers for Disease Control (CDC), 2014; Mitchell et al, 2013;Sternthal, Jun, Earls, & Wright, 2010). The Adverse Childhood Experience (ACE) Study assessed over 17,000 participants to examine the long-term effects of violence and trauma on biological, social, and psychological outcomes (CDC, 2014).…”
Section: Impact Of Violence and Trauma On Childrenmentioning
confidence: 99%